Dementia : comprehensive principles and practice - Dickerson, Bradford C.; Atri, Alireza (Oxford University Press, 2014)
Dementia: Comprehensive Principles and Practice is a clinically-oriented book designed for clinicians, scientists, and other health professionals involved in the diagnosis, management, and investigation of disease states causing dementia. A ""who's who"" of internationally-recognized experts contribute chapters emphasizing a multidisciplinary approach to understanding dementia. The organization of the book takes an integrative approach by providing three major sections that (1) establish the neuroanatomical and cognitive framework underlying disorders of cognition, (2) provide fundamental as well as cutting-edge material covering specific diseases associated with dementia, and (3) discuss approaches to the diagnosis and treatment of dementing illnesses.